(untitled) (Communications in Computational Physics, 2019)
In this paper, we propose and analyze a Müntz spectral method for a class of two-dimensional space-fractional convection-diffusion equations. The proposed methods make new use of the fractional polynomials, also known as Müntz polynomials, which can be regarded as continuation of our previous work. The extension is twofold. Firstly, the existing Müntz spectral method for fractional differential equation with fractional derivative order 0